Ethanol production from cassava stem in Vietnam potential of CO2 emission reduction aspect and an efficient ethanol production process - Pham, Thi Pham
Reducing carbon dioxide emission and using renewable clean fuels have been among the strategies for addressing climate change and depleting fossil fuel reserve issues. Converting cassava farm wastes to bioethanol instead of burning them or allowing them to decay on open fields can contribute to efforts on reducing CO2 emission and fossil fuel use. In Vietnam, cassava crop farms is second to rice farms in terms of land area and, as determined in this study, also in the amount of biomass waste generated (ca. 1.12 million ton ethanol/year, in 2014). This study determined to potential of bioethanol production and CO2 emission reduction from cassava stem (CS) in Vietnam. The corresponding reduction in CO2 emission for producing and using bioethanol from CS is 9.1 million tons/year, which is 3.7 percent of the national emission in 2010. This study also aimed to develop a simple and efficient process for ethanol production from CS. Separate hydrolysis and fermentation (SHF) process for bioethanol production from CS was applied. To get sugars from CS for ethanol fermentation, a two stage sulfuric acid hydrolysis was used. For this part, a combination of acid-to-substrate ratio, temperature and reaction time that results in lower furfural level (0.83 ± 0.12 g/L) and high sugar recovery (74.7 ± 7.7 percent) from 150 g CS/L was obtained. Furfural tolerant yeast Saccharomyces cerevisiae IAM 4178 was used on hydrolysate of 200 g CS/L without removing furfural and other potential inhibitors. High ethanol concentration (23.7 g/L or 3 percent v/v), high productivity (2 g/L/h) and ethanol yield of 71 percent were achieved